2006
DOI: 10.1080/17470210600784649
|View full text |Cite
|
Sign up to set email alerts
|

Scalar Properties in Animal Timing: Conformity and Violations

Abstract: The article reviews data from animal subjects on a range of timing tasks (including fixed-interval and temporal differentiation schedules, stimulus timing, aversive conditioning, and Pavlovian methods) with respect to conformity to the two scalar properties of timing behaviour: mean accuracy and scalar (Weberian) variance. Systematic deviations were found in data from temporal differentiation schedules, timing of very short (<100 ms) or very long (>100 s) durations, effects of "task difficulty", and some speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
111
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(118 citation statements)
references
References 147 publications
(204 reference statements)
4
111
0
3
Order By: Relevance
“…Research on prospective timing has shown that prospective duration memory is systematically less precise for longer durations [33,34]. This so-called scalar property is apparent when subjects are asked to make estimates about durations encoded into memory.…”
Section: Cognitive Processes That Underlie Prospective Duration Memorymentioning
confidence: 99%
“…Research on prospective timing has shown that prospective duration memory is systematically less precise for longer durations [33,34]. This so-called scalar property is apparent when subjects are asked to make estimates about durations encoded into memory.…”
Section: Cognitive Processes That Underlie Prospective Duration Memorymentioning
confidence: 99%
“…Although SET predicts that the CV should be constant over time (Lejeune & Wearden, 2006)-a prediction that holds with nonmusicians in both mediator and nonmediator conditions-the CV of musicians decreased with interval length. also reported a violation of the simple Weber's law in a counting condition but reported no specific musical abilities of their subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The pacemaker-counter model currently most popular, scalar expectancy theory (SET; Gibbon, 1991Gibbon, , 1992Gibbon, Church, & Meck, 1984;Lejeune & Wearden, 2006), recognizes that the standard deviation (SD) of estimates typically increases as a linear function of the magnitude of the duration to be judged, a property known in psychophysics as Weber's law and in SET as the scalar property of timing. According to Weber's law, the Weber fraction (w) is invariant over the magnitude of the stimuli discriminated.…”
mentioning
confidence: 99%
“…Long-FI response gradients There are two characteristic properties of responding in simple FI schedules: scalar timing and scalar variance (Lejeune & Wearden, 2006). With scalar timing, the center of the response gradient is proportional to the duration of the interval.…”
Section: Discussionmentioning
confidence: 99%